Development of adversity quotient based geometry learning model for prospective teachers - Sudarman Bennu; Akina Akina (International Journal on Teaching and Learning Mathematics, 2019)
The objective of this research is to develop the adversity quotient-based and media-assisted model of mathematics teaching. The stages follow Plomp Model that involves (1) preliminary study, (2) designing (planning), (3) realization/ construction, (4) test, evaluation and revision, (5) implementation. Stages 1 through 3 were held in 2017, stages 4 and 5 completed in 2018 and 2019. Through the preliminary study, designing, and realization/construction, the researchers were able to construct the model in five components: syntax, social system, reaction principles, supporting system, and instructional and nurturing effect. The syntax of this model covers: introduction of learning objectives, motivating, the presentation of prerequisite material and the discussion structured task, student categorization based on adversity quotient, group discussion, group presentation, concluding the discussion, evaluation, and assigning structured-tasks individually and in groups.